The Art of Quranic Phrasing: An Exploration of Its Names and Significance (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The research discusses the names of the Quran, highlighting their significance and the various descriptions attributed to the Quran. It emphasizes that these names are fitting for the divine book, both in meaning and language. The study explores how these names and descriptions align with the Quran's content and purpose, providing a deeper understanding of its linguistic and theological aspects.